Risk Assessment in Prisons: Theory and the Hungarian Practice - Somogyvári, Mihály (Magyar Rendészet, 2024)
The aim of this paper is to briefly present a theoretical background of risk assessment systems in prisons and their practice in Hungary. Besides presenting the theoretical framework, I will discuss the purpose and methodological framework of risk assessment for inmates and the main institutional approaches used in international practice. In the second part of the paper, I will present the national practice, its methodological specifics and institutional framework.